2020
DOI: 10.2478/aut-2020-0020
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Assessment of the Properties of Cotton Single Jersey Knitted Fabrics Produced From Different Lycra States

Abstract: AbstractThis research aims to evaluate the properties of cotton single jersey knitted fabrics (SJKF) produced from cotton/spandex yarns at different Lycra states. So, four different SJKF were produced, namely 100% cotton, cotton with additional Lycra (full-platted), core, and dual-core-spun (DCS) yarns with the same loop length. The thermal comfort properties, fabric recovery, total hand value (THV), moisture management parameters, and air permeability were measured. The experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 16 publications
1
12
0
Order By: Relevance
“…The thermal resistance of fabrics can be calculated by means of experimental, analytical, and numerical methods [16,17]. There are many models to be found within the textile engineering and heat transfer fi elds for the thermal resistance prediction.…”
Section: Thermal Resistance Models and Their Applicationsmentioning
confidence: 99%
“…The thermal resistance of fabrics can be calculated by means of experimental, analytical, and numerical methods [16,17]. There are many models to be found within the textile engineering and heat transfer fi elds for the thermal resistance prediction.…”
Section: Thermal Resistance Models and Their Applicationsmentioning
confidence: 99%
“…Single jersey knitted fabrics (SJKF) are used for under-and outer-wear compared to woven fabrics because of their high extensibility (compression and elongation of individual stitch) [4]. To enhance the dimensional stability and maintain the dimensions during use and after repeated stresses of knitted fabrics, the additional Lycra (full-and halfplaited) and core-spun yarn are used [5]. Lycra is the trade name of elastane (spandex) yarns.…”
Section: Introductionmentioning
confidence: 99%
“…It was noticed that the air permeability, total hand value, overall moisture management capacity, and the water vapor permeability of stretched SJKF are lower than the corresponding values for 100% cotton fabric sample. Thermal absorptivity of core and dual-core samples increased when compared to 100% cotton fabric sample [5]. The thermal comfort properties of SJKF produced from cotton/Lycra core spun yarn and cotton/additional Lycra ( fp) were investigated.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The researchers concluded that the permeability properties of the knitted fabrics produced with cotton, viscose, and PES fibres in the sheath and PVA in the core were positively affected [31]. Khalil et al [2020] studied the thermal comfort properties of 100% cotton, cotton with full-platted Lycra, Core, and Dual Core spun yarns (DCS). It is concluded that the core spun and DCS show the highest elongation 27% increased thermal conductivity 18% decreased water-vapour permeability which gives extensibility and comfort at the same strength compared to 100% cotton samples [32].…”
Section: Introductionmentioning
confidence: 99%